2011
DOI: 10.1007/s13277-011-0280-4
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 6 (PDCD6) as a prognostic marker for gastric cancers

Abstract: Programmed cell death 6 (PDCD6) plays an important role in apoptotic cell death and tumorigenesis. In this study, we investigated whether PDCD6 contributes to the development and/or progression of gastric cancers. PDCD6 protein expression was examined in 169 advanced gastric cancer specimens by immunohistochemistry and then correlated with clinicopathologic parameters. We also analyzed mutations, methylation status, and alterations in DNA copy number and mRNA transcripts, and protein expression of PDCD6 in gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
(30 reference statements)
3
17
0
Order By: Relevance
“…These resistance isolates had their own antifungal resistance profiles, indicating that these mutations may have originally existed in the A. fumigatus strain and also suggesting that evolved lineages (isolates) may acquire azole resistance independently, while algA defects made the drug-resistant alleles much easier to isolate. Since the algA homolog in humans has a role in apoptotic cell death, this suggests that the loss of algA in fungal cells may allow them to more easily escape from cell apoptosis induced by itraconazole and result in survival mutants conferring drug resistance (33). In addition, of 11 selected independent itraconazole-resistant representatives, we found that they all had various MEC values of caspofungin, suggesting that the cell wall synthesis-related drug target of caspofungin in some isolates may be changed.…”
Section: Discussionmentioning
confidence: 99%
“…These resistance isolates had their own antifungal resistance profiles, indicating that these mutations may have originally existed in the A. fumigatus strain and also suggesting that evolved lineages (isolates) may acquire azole resistance independently, while algA defects made the drug-resistant alleles much easier to isolate. Since the algA homolog in humans has a role in apoptotic cell death, this suggests that the loss of algA in fungal cells may allow them to more easily escape from cell apoptosis induced by itraconazole and result in survival mutants conferring drug resistance (33). In addition, of 11 selected independent itraconazole-resistant representatives, we found that they all had various MEC values of caspofungin, suggesting that the cell wall synthesis-related drug target of caspofungin in some isolates may be changed.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis serves an important role in the progression of ovarian cancer (13), and certain papers have suggested that human chorionic gonadotropin or LH may inhibit cisplatin-induced apoptosis in ovarian cancer cells (14,15). PDCD6 is an important apoptotic mediator and a prognostic marker for gastric cancer (16); it is also an independent predictor of progression-free survival in patients with epithelial ovarian cancer (7). Park et al (17) demonstrated that PDCD6 additively cooperated with anticancer drugs through the activation of nuclear factor-κB pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, some important factors should be noticed. For example, one of down-regulated protein, programmed cell death protein 6 (PDCD6), also called apoptosislinked gene 2 protein (ALG2), functions as calciumbinding protein required for T cell receptor-, Fas-, and glucocorticoid-induced cell death (Suzuki et al 2012;Yoon et al 2012). Besides their multifunction, four proteins, ATP-dependent RNA helicase DDX39A, complement component 1 Q subcomponent-binding protein (SF2p32), Lamin-A/C, and far upstream element-binding Protein 2 are involved in pre-mRNA splicing or as splicing factors to play an important role in DNA damage and repair (Dittmer and Misteli 2011;Filippov et al 2007;Marengo and Wassarman 2008;Singh et al 2013).…”
Section: Discussionmentioning
confidence: 99%